Relação entre riscos socioeconômicos e clínicos e apoio social: uma estratégia para promoção de saúde - Nunes, Marilene Rivany (2009)
Background: Health promotion proposals for communities should consider the environmental, social and economic determinants that are associated with the familiesí way of life. The literature shows that social support can contribute to strengthen the coping strategies of families and lead to health promotion. Objectives: Identify the relation between the socioeconomic and clinical risk conditions of families and the social support acknowledged by families attended by the Family Health Services in a Brazilian community. Methods: This is a pilot study based on a random sample survey. An instrument was developed based on literature review aiming to assess the perception of family members about social support according to the following dimensions: instrumental, emotional, religious and support received from friends, neighbors and family. The families were previously categorized into low, medium and high risk according to their socioeconomic and clinical risk type. The data were treated by descriptive statistics and compared by means of the Chi-square test (˜ 2 ), p ≤ 0.05. Setting and Sampling: Families were selected by stratified random sampling from a list provided by the Family Health Unit (N = 162). A total of 59 families participated in the study, distributed as follows: eight at low risk, 28 at medium and 23 at high risk. All the family members who had agreed to participate were interviewed, totaling 164 participants older than 12 years. Research Ethics: The project was approved by an Ethics Committee for Research with Human Subjects. Results and Conclusions: The families averaged 3.25 members. The members from families at higher risk were shown to perceive receiving more instrumental support (p=0.050), but no evidence showed that religious (p=0.215), emotional (p=0.215) and family support (p=0.451) was related to socioeconomic and clinical risk. This suggests that socioeconomic differences and clinical risk do not influence the values attributed to those types of supports. However, evidence showed that the perception of families at higher risk levels was higher in relation to support received from friends and neighbors (p=0.015). Conclusion: Knowledge on the perception of the social support acknowledged by families can help health professionals to design strategies to help families at socioeconomic and clinical risk to cope with their living conditions. Studies with larger number of participants are suggested in order to enable generalizations and broaden knowledge about the types of social support which are acknowledged as valuable by vulnerable families.